Evaluation of the results assessing motor abilities of boys and girls aged 11-14 during selection in rowing - Oreb, G.; Zovic, M.; Marelic, N. (Acta Kinesiologica, 2008)
The goal of this work was to confirm whether or not the chosen form of tests for evaluation of motor skills can be an indicator for the purpose of selection of children in rowing. The test sample was made up of 266 boys and 170 girls aged 11 to 14. The testees were examined by the tests for evaluation of motor abilities as follows: the speed of movement frequency (MTR), initial burst of strength (MSD), coordination (MTR), repetitive strength (MPT15s), flexibility (MPR), static strength (MIV) and also by the test for evaluation of specific abilities when the rowing ergometer Concept II was used at the distance of 500 meters simulating perfectly the conditions of rowing on water. It was confirmed that explosive strength, flexibility and coordination were the most important factors predicting the success of the boys when using the ergometer at a distance of 500 meters, while for the girls, the most important factors were flexibility, explosive strength, speed and repetitive strength. Among the boys, the multiple correlation coefficient was 0,50 while among the girls, it was 0,53, with a statistically significant error of p< 0,00. The joint variability of the predictable variables and criteria among the boys was 0,25 while among the girls, it was 0,28. The largest correlation coefficient with criteria was evident for the male students in the tests of explosive strength (MSD) with the value of -0,25, whereas the same, for the female sample, was flexibility (MPR), with a value of -0,32. The results show that by using selection, we can include the motor-skill testing used in the education system of primary schools, keeping in mind the importance of the testing difference between male and female.